The Influence of Social Media on Arabic Language Change in Online Communication - Nabilah, Nailin; Mufidah, Harini Nur; Nafisah, Shofi; Baihaqi, M.; Ulin Nuha, Ahmad Nur; Sa'adi, Zainur Rohmah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
This research aims to investigate the changes in Arabic language in online communication caused by social media. Social media, as a platform for online communication connecting people worldwide, has influenced contemporary life. One of the most common impacts is language change. Therefore, this research will focus on examining the influence of social media on Arabic language change, especially in online communication. The research method employed is qualitative. Data were obtained from active users of Instagram and YouTube who communicate in Arabic. Data collection techniques involved observation and questionnaires, while data analysis utilized narrative analysis. The results indicate that social media significantly influences the shift in Arabic language from fushha> to ‘a>miya in online communication. Out of 52 respondents, 43 stated that social media has a negative impact on language change in online communication. Colloquial Arabic is preferred due to its perceived informality and relaxed nature, yet classical Arabic remains important for formal contexts.